Analysis of Prophylactic Antibiotics Usage in Caesarean Section Delivery - Muzayyanah, Binti; Yulistiani, Yulistiani; Hasmono, Didik; Wisudani, Nuraida (Folia Medica Indonesiana, 2018)
Caesarean section is the delivery through a surgical incision in the abdomen and uterus with various risks, such as Surgical Site Infection (SSI) which either occurs rapidly (24-48 hours postoperatively) or delayed. To reduce the risk of various post-cesarean section infections, prophylactic antibiotics are given. The administration of prophylactic antibiotics with recommended regimens, such as in developed countries as in the United States and Europe, with first generation of cephalosporins has not been applied in Dr. Iskak Hospital, Tulungagung. This hospital still used other types of antibiotics, such as cefotaxime or ceftriaxone. In addition, for several reasons, prophylactic antibiotics were continued with other antibiotics to reduce the risk of delayed infection. This study was designed to analyze the effectiveness of prophylactic antibiotics as recommended in cesarean section. This was a prospective observational study with consecutive sampling type, examined 41 mothers with cesarean section at the Department of Obstretics and Gynecology, Dr. Iskak Hospital, Tulungagung, Indonesia. This study was conducted from May to July, 2017. The results of the study showed that the effectiveness of prophylactic antibiotic use was 98% based on the clinical parameters and maternal laboratory outcome, which showed that SIRS was in normal category. Whereas, there was one mother (2%) who had SSI on day 10 postoperatively.